The Rules of Fiqh Al-Adatu Muhakkam in the Tradition of "Menjalang" and "Mandi Balimau Kasai" in Parit Baru Village - Khairul Akmal (International Journal of Social Service and Research, 2023)
The conclusion of this study highlights the intricate interplay between religious and cultural aspects within Indonesian society, particularly in the context of Parit Baru village. The village's adherence to ancient customs like the Menjalang tradition and the Balimau Kasai Bathing tradition reflects a commitment to both religious values, primarily Islam, and the preservation of unique cultural practices. The Menjalang tradition, considered a silaturrahim practice, fosters family unity and forgiveness as a precursor to the holy month of Ramadan. Its alignment with Islamic teachings and emphasis on familial solidarity make it a meaningful practice. Similarly, the Balimau Kasai Bathing tradition, while not strictly obligatory according to Islamic teachings, maintains its significance in welcoming Ramadan. The tradition embodies the intersection of cultural heritage and religious observance, with the possibility of evolving into a Sunnah practice. This study underscores how local customs can harmonize with religious norms, enriching the diverse tapestry of Indonesian society while maintaining alignment with Islamic principles.